Pingo Canadian Landmark. Ultra high resolution orthomosaic. - Vieira, Gonçalo; Pina, Pedro; Whalen, Dustin; Freitas, Pedro; Pinheiro, Daniel; Fraser, Paul; Robertson, Angus; Berry, Heather B. (Zenodo, 2020)
Ultra high resolution orthomosaic (Poster A0) of Pingo Canadian Landmark surveyed in July-August 2019.